Control interno al sistema de inventario y su incidencia en la rentabilidad de ecopanal año 2023 - Merizalde Zamora , Fernanda Carolina (2024)
The general objective of the research was to analyze the administration of the internal control of the inventory system and its impact on the profitability of ECOPANAL, Quevedo canton, period 2023; The research is qualitative, quantitative, field research, descriptive and analytical, methods such as deductive and inductive analysis were used, in addition, instruments were developed that were applied in the area, such as the interview, the ABC method was applied, inventory valuation and efficiency and effectiveness indicators, in addition, the impact of profitability on the economy of the business was evaluated by analyzing the factors that affect the adequate control of stocks, as well as opportunities for improvement to have a physical stock, kardex up to date. As a result, the inventory area is based on empirical knowledge, resulting in the development of the ABC method 78% corresponding to category A which is the total value on sales, 15% in category B and 7% for category C, they do not have an established valuation method for inventories, which is why in the development of the second objective it gives us a gap of 1.45% of profit margin of the average method on the PEPS, the efficiency and effectiveness indicators show a negative result to the established goal, both indicators under 90% compliance, As conclusions, the administration in inventory controls presents weaknesses, it is recommended to train staff on continuous improvement of internal control processes of financial information, update inventory, prices, products based on organizational requirements, obtain a management manual to strengthen efficiency and effectiveness indicators.